Pengelolaan Tata Tertib Sekolah Menengah Pertama - Anggraini, Eka Novia; Subadi, Tjipto (Jurnal VARIDIKA, 2015)
The purpose of this study was to describe the planning, organizing, and monitoring the enforcement of school rules in Junior High School 9 Surakarta. Qualitative research with ethnographic design. Research place in Junior High School 9 Surakarta. When the study May to December 2015. The subjects of the research principal, vice principal of student, counseling teachers, teachers, order officers, and students. Data collection techniques through observation, interviews, and documentation. The interview process used is first order and second order understanding understanding. Validity of the data with source triangulation, triangulation method, and triangulation of time. Data analysis techniques with methods groove. Results of the study (1) The planning process of school discipline is done with deliberation involving the principal, vice principal of student, counseling teachers, and teachers, (2) The process of familiarization of the school rules made explanations during the orientation of students, books discipline students, board regulations, as well as the subjects of counseling, (3) Implementation of enforcement of school rules based on awarding points, the type of violation, as well as development, (4) Monitoring and evaluation order continuously conducted to determine the follow-up will be done school to maximize enforcement of school rules.